2018
DOI: 10.3310/hta22170
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine for people with borderline personality disorder: a RCT

Abstract: BackgroundNo drug treatments are currently licensed for the treatment of borderline personality disorder (BPD). Despite this, people with this condition are frequently prescribed psychotropic medications and often with considerable polypharmacy. Preliminary studies have indicated that mood stabilisers may be of benefit to people with BPD.ObjectiveTo examine the clinical effectiveness and cost-effectiveness of lamotrigine for people with BPD.DesignA two-arm, double-blind, placebo-controlled individually randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 68 publications
0
14
1
Order By: Relevance
“…However, a more recent 52-week, two-arm, double-blind, large-scale multicenter RCT comparison of lamotrigine versus placebo in BPD patients failed to show significant superiority of lamotrigine [ 94 ]. This evidence underlines that lamotrigine is not clinically or more costly effective than the usual care in BPD subjects [ 94 , 95 ]. In brief, although several studies showed that lamotrigine had shown evidence of efficacy in reducing aggressive symptoms, affective lability, and impulsivity in BPD, the most extensive study failed to find any effect at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent 52-week, two-arm, double-blind, large-scale multicenter RCT comparison of lamotrigine versus placebo in BPD patients failed to show significant superiority of lamotrigine [ 94 ]. This evidence underlines that lamotrigine is not clinically or more costly effective than the usual care in BPD subjects [ 94 , 95 ]. In brief, although several studies showed that lamotrigine had shown evidence of efficacy in reducing aggressive symptoms, affective lability, and impulsivity in BPD, the most extensive study failed to find any effect at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, most reports are based on studies with patients presenting not only borderline PD but also, for example, bipolar II disorder. Therefore, a special consideration merits the recent study of Crawford et al (2018a), which was based on a well-elaborated methodology (Crawford et al 2015(Crawford et al , 2018b. They described the effect of lamotrigine in a group of borderline PD patients, from which bipolar patients were excluded: They concluded that this anticonvulsant and mood-stabilizing drug is not a clinically effective or costeffective treatment.…”
Section: Mood Stabilizersmentioning
confidence: 99%
“…As requested, we have examined mean scores on the Zanarini Rating Scale for Borderline Personality Disorder (ZAN-BPD) at 12 weeks in subsamples of people who were adherent with medication during this period, those without coexisting substance misuse, and those who had a recent history of deliberate self-harm. While conducting this analysis, we identified a typographical error that appeared in our article (1) but not in the monograph that has subsequently been published that provides additional information about the trial (2). The number of participants in the placebo arm of the trial who reported deliberate self-harm in the 6 months prior to randomization was 87 (63%), not 51 (37%) as erroneously stated in our article.…”
mentioning
confidence: 93%
“…The second measured but unaccounted for confounding effect stemmed from the inclusion of subjects with schizoaffective disorder. Compared with schizophrenia, schizoaffective disorder may have better outcomes (2). The authors could have mentioned and compared the number and distribution of subjects with schizoaffective disorder among the users and discontinuers to examine the effect of this potential confounder.…”
mentioning
confidence: 99%